2007
DOI: 10.1016/j.brainres.2007.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of FGF-2 with IGF-1 and BDNF in stimulating Akt, ERK, and neuronal survival in hippocampal cultures

Abstract: The significance of multiple growth factors acting on individual neurons in the central nervous system is presently unclear. Cultured hippocampal neurons were used in the present study to compare the neurotrophic actions of fibroblast growth factor-2 (FGF-2) with the better characterized growth factors, insulin-like growth factor (IGF)-1 and brain-derived neurotrophic factor (BDNF). Additionally, cultures were utilized to identify possible interactions between FGF-2 and the other growth factors. Activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…In contrast, pretreatment with the ERK inhibitor, U0126, did not have effect on the neuroprotection induced by FGF2. Thus our data revealed that AKT but not ERK signaling pathway was involved in the FGF2 mediated neuroprotection in an AD model, this is consistent with the previous study showing that AKT is required for FGF-2-stimulated survival in primary cultured hippocampal neurons [34]. Since our data did not show significant difference between HMW and LMW FGF2 mediated ERK and AKT activation, the stronger neuroprotective effect induced by HMW FGF2 may be mediated by the other signals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, pretreatment with the ERK inhibitor, U0126, did not have effect on the neuroprotection induced by FGF2. Thus our data revealed that AKT but not ERK signaling pathway was involved in the FGF2 mediated neuroprotection in an AD model, this is consistent with the previous study showing that AKT is required for FGF-2-stimulated survival in primary cultured hippocampal neurons [34]. Since our data did not show significant difference between HMW and LMW FGF2 mediated ERK and AKT activation, the stronger neuroprotective effect induced by HMW FGF2 may be mediated by the other signals.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that FGF2 can activate ERK and AKT in the primary cultured hippocampal neurons [34]. In addition, both ERK and AKT signaling pathways are well known for the major roles in mediating the neuroprotective actions of neurotrophic factors [2022].…”
Section: Discussionmentioning
confidence: 99%
“…60 Interestingly, FGF-2 promotes differentiation of resident cardiac precursors into functional cardiomyocytes, 61 which would seem at odds with maintenance of a proliferative state unless the action of FGF-2 occurs at an early stage of commitment, when limited mitotic activity occurs in concert with lineage specification. FGF-2 stimulates Akt activity that could account for prosurvival and proproliferative effects, [62][63][64] and Akt activation lies upstream from Pim-1 induction in cardiomyocytes. 31 Induction of nucleostemin expression by Pim-1 activity ( Figure 6) is without precedent in the literature and reveals an important mechanistic basis for Pim-1-mediated promotion of proliferation in the myocardium that will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several insulin signaling molecules play essential roles in synaptic plasticity [68], suggesting their role in learning and memory. Activation of insulin receptors result in downstream activation of the phosphatidylinositide 3 kinase (PI3)/Akt pathway [69], an important signaling pathway for synaptic plasticity [70]. Akt inactivates GSK-3β by phosphorylation of the serine-9 residue.…”
Section: Stz-induced Kinase Activationmentioning
confidence: 99%